Retinal proteome changes following experimental branch retinal vein occlusion and intervention with ranibizumab. (November 2016) - Cehofski, Lasse Jørgensen; Kruse, Anders; Bøgsted, Martin; Magnusdottir, Sigriður Olga; Stensballe, Allan; Honoré, Bent; Vorum, Henrik
Abstract: Animal models of experimental branch retinal vein occlusion (BRVO) provide a unique opportunity to study protein changes directly in retinal tissue. Results from these experimental models suggest that experimental BRVO is associated with an upregulation of extracellular matrix remodeling and adhesion signaling processes. To study whether these processes could be blocked by inhibition of VEGF-A, a porcine model of experimental BRVO was combined with proteomic analyses. In six Danish Landrace pigs experimental BRVO was induced with argon laser in both eyes. After 24 h an injection of 0.05 mL ranibizumab was given in the right eyes of the animals while left eyes received an injection of 0.05 mL 9 mg/mL sodium chloride water. Retinas were dissected three days after BRVO and the retinal samples were analyzed with label-free quantification as well as tandem mass tag based proteomics. In retinas treated with ranibizumab five proteins exhibited statistically significant changes in content with both proteomic techniques. These five proteins, which were all decreased in content, included integrin β-1, peroxisomal 3-ketoacyl-CoA thiolase, OCIA domain-containing protein 1, calnexin and 40S ribosomal protein S5. As anti-integrin therapies are under development for inhibition of angiogenesis in retinal diseases it is interesting that inhibition of VEGF-A in itself resulted in a small decrease in the content of integrin β-1. The decreased content of integrin β-1 indicates that extracellular matrix remodeling and adhesion processes associated with BRVO are at least partly reversed through inhibition of VEGF-A. Graphical abstract: Highlights: The content of integrin β-1 was decreased following treatment with Ranibizumab. Calnexin and 40S ribosomal protein S5 decreased in content when VEGF-A was blocked. OCIA domain-containing protein 1 was downregulated following inhibition of VEGF-A. A role of integrin β-1 in branch retinal vein occlusion is proposed.